‘The Research is Conducted…’: An Exploration of a Grammatical Metaphor Syndrome in Indonesian Research Articles - Putu Nur Ayomi; Shoshana Dreyfus; Syamsul Hadi; Adi Sutrisno (Lingua Cultura, 2020)
The research examined the use of one grammatical metaphor (hereafter GM) syndrome frequently found in Indonesian language research articles (hereafter RAs). This syndrome followed the lexicogrammatical structure of Process+Range or Process+Medium. An interesting feature of this GM syndrome, which, to date, had not been studied, was that while GM typically increased the lexical density of a clause by condensing meaning into nominal groups. This GM syndrome seemed to do the opposite. e.g., rather than writing ‘merubah’ (changed) as Process, writers used ‘melakukan perubahan’ (do some changes), which had the structure of Process+Range. This had the effect of delexicalizing the verb as well as increasing the number of words in the clauses. Instead of seeing this form as a mere ritual in academic writing, the research sought to understand the functional role in the RAs. The data was taken from a small corpus of RAs from two refereed Indonesian humanities journals. The occurrences of this GM syndrome were identified. A systemic analysis was then conducted with a metafunctional lens, examining the ideational, interpersonal, and textual functions of this form of GM syndrome. The analysis reveals that ideationally, GM syndrome is a resource to manage technicality, abstraction, taxonomy, and activity sequence; textually, the syndrome is a resource organizing textual coherence through the management of hyperThemes; and interpersonally, the syndrome functions as a resource for Graduation, which decreases the force of propositions.